Calibration of strain gauged square tunnels for centrifuge testing - Tsinidis, Grigorios; Heron, Charles; Madabhushi, Gopol; Pitilakis, Kyriazis (Springer Verlag, 2016)
A series of dynamic centrifuge tests were conducted on square aluminum model tunnels embedded in dry sand. The tests were carried out at the Schofield Centre of the Cambridge University Engineering Department, aiming to investigate the dynamic response of these types of structures. An extensive instrumentation scheme was employed to record the soil-tunnel system response, which comprised of miniature accelerometers, total earth pressures cells and position sensors. To record the lining forces, the model tunnels were strain gauged. The calibration of the strain gauges, the data from which was crucial to furthering our understanding on the seismic performance of box-type tunnels, was performed combining physical testing and numerical modelling. This technical note summarizes this calibration procedure, highlighting the importance of advanced numerical simulation in the calibration of complex construction models.